Effect of a Rho Kinase Inhibitor on Cognitive Impairment Induced by Chronic Cerebral Hypoperfusion in Rats - Zhang, Q.; Zhang, J. -J.; Han, Zh. -M. (Нейрофизиология, 2015)
We examined the efficacy of a Rho kinase inhibitor, Fasudil, on cognitive impairment induced by
chronic cerebral hypoperfusion in rats. Thirty-two male adult Sprague-Dawley rats were randomly divided into three groups; treated (T), control (C), and sham-operated (Sh); severe stenosis of
the carotid arteries was modeled in the former two groups. During two weeks, 8.35 mg/kg Fasudil
and physiological saline were i.p. applied twice per day in the T and C groups, respectively. The
Morris water maze test was performed in each group to detect changes in the cognitive function
and to observe pathological shifts in hippocampal morphology in rats after eight weeks. The mean
escape latency was distinctly shorter (P < 0.01), and the percentage of swimming distance within
the platform quadrant was significantly greater (P < 0.01) in the T group, compared to those in the
C group at the corresponding time points. The rate of carotid artery stenosis in rats demonstrated
no statistical difference between the T and C groups (P > 0.05). Fasudil injections effectively normalized hippocampal pathomorphology in the T group. Thus, the Rho kinase inhibitor obviously
ameliorated cognitive impairment induced by chronic cerebral hypoperfusion in rats. Ми досліджували вплив інгібітора Rho-кінази фасудилу на
когнітивні ураження, індуковані у щурів хронічною недостатністю перфузії мозку. 32 дорослі самці щурів СпрейгДоулі були рандомізовано поділені на три групи – “ліковану” (Т), контрольну (С) та псевдооперовану (Sh); у двох
перших групах був модельований важкий стеноз сонних артерій. Протягом двох тижнів щурам груп Т і С внутрішньоочеревинно уводили двічі на день відповідно фасудил у дозі
8.35 мг/кг та фізіологічний розчин. Тварини всіх груп піддавали тесту Морріса у водному лабіринті, щоб виявити
зміни когнітивної функції; у цих щурів спостерігали також
патологічні зрушення морфології гіпокампа через вісім тижнів. У групі Т середній латентний період початку рухів уникання ставав істотно коротшим (P < 0.01), а нормована відстань переміщень у квадранті з платформою була вірогідно
більшою (P < 0.01), ніж аналогічні показники у відповідних
часових інтервалах у групі С. Ступінь стенозу сонних артерій у щурів груп Т та С не демонстрував істотних відмінностей. Ін’єкції фасудилу призводили до істотної нормалізації патоморфологічних зрушень у гіпокампі тварин групи
Т. Отже, інгібітор Rho-кінази забезпечував явне зменшення
уражень когнітивної сфери, індукованих у щурів хронічною
гіпоперфузією мозку.